Renaissance & reformation : biographies - Saari, Peggy; Saari, Aaron Maurice (Detroit : U. X. L., 2002)
Profiles fifty people who played a significant role during the Renaissance and Reformation periods in Europe, including John Calvin, Peter Paul Rubens, Catherine de Medici, and Johannes Kepler.
v. 1. A-K -- v. 2. L-Z
Includes bibliographical references and index.
Keywords: Renaissance -- Biography -- Juvenile literature; Reformation -- Biography -- Juvenile literature; Renaissance -- Biography; Reformation -- Biography; Europe -- Biography -- Juvenile literature; Europe -- Biography